In vivo expression of Nurr1/Nr4a2a in developing retinal amacrine subtypes in zebrafish Tg(nr4a2a:eGFP) transgenics. Issue 8 (15th March 2017) - Goodings, Liana; He, Jie; Wood, Alasdair J.; Harris, William A.; Currie, Peter D.; Jusuf, Patricia R.
Abstract: The Nuclear receptor subfamily 4 group A member 2 (Nr4a2) is crucial for the formation or maintenance of dopaminergic neurons in the central nervous system including the retina, where dopaminergic amacrine cells contribute to visual function. Little is known about which cells express Nr4a2 at which developmental stage. Furthermore, whether Nr4a2 functions in combination with other genes is poorly understood. Thus, we generated a novel transgenic to visualize Nr4a2 expression in vivo during zebrafish retinogenesis. A 4.1 kb fragment of the nr4a2a promoter was used to drive green fluorescent protein expression in this Tg( nr4a2a:eGFP ) line. In situ hybridization showed that transgene expression follows endogenous RNA expression at a cellular level. Temporal expression and lineages were quantified using in vivo time‐lapse imaging in embryos. Nr4a2 expressing retinal subtypes were characterized immunohistochemically. Nr4a2a:eGFP labeled multiple neuron subtypes including 24.5% of all amacrine interneurons. Nr4a2a:eGFP labels all tyrosine hydroxylase labeled dopaminergic amacrine cells, and other nondopaminergic GABAergic amacrine populations. Nr4a2a:eGFP is confined to a specific progenitor lineage identified by sequential expression of the bhlh transcription factor Atonal7 (Atoh7) and Pancreas transcription factor 1a (Ptf1a), and labels postmitotic postmigratory amacrine cells. Thus, developmental Nr4a2a expression indicates a role during late differentiation of specific amacrine interneurons. Tg( nr4a2a:eGFP ) is an early marker of distinct neurons including dopaminergic amacrine cells. It can be utilized to assess consequences of gene manipulations and understand whether Nr4a2 only carries out its role in the presence of specific coexpressed genes. This will allow Nr4a2 use to be refined for regenerative approaches. Abstract : The Nuclear receptor 4 subunit 2a (Nr4a2a) is expressed in post‐mitotic, post‐migratory developing retinal neurons, suggesting a role in late differentiation or survival. Additional to dopaminergic amacrine interneurons (tyrosine hydroxylase immunoreactive), which are known to require Nr4a2, retinal ganglion cells and other GABAergic amacrine interneurons also express Nr4a2, revealing potential additional neurodevelopmental roles of Nr4a2.